Peroxisome proliferator-activated receptor (PPAR) α and δ activators induce ICAM-1 expression in quiescent non stimulated endothelial cells. Issue 1 (December 2016) - Naidenow, Julia; Hrgovic, Igor; Doll, Monika; Hailemariam-Jahn, Tsige; Lang, Victoria; Kleemann, Johannes; Kippenberger, Stefan; Kaufmann, Roland; Zöller, Nadja; Meissner, Markus
Abstract Background Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that are implicated in the regulation of lipid and glucose homeostasis. PPAR agonists have been shown to control inflammatory processes, in part by inhibiting the expression of distinct proinflammatory genes such as vascular cell adhesion molecule-1 (VCAM-1), IL-8, and intercellular adhesion molecule-1 (ICAM-1). ICAM-1 is an important endothelial membrane receptor that facilitates the transmigration of leukocytes across the endothelium. To date, the influence of PPARα and δ activators on the expression of ICAM-1 in non-induced, quiescent endothelial cells has been unclear. Therefore, we examined the effects of various PPARα and δ agonists on the expression of ICAM-1 in non-stimulated primary human endothelial cells. Results We found that PPARα and PPARδ agonists significantly induced ICAM-1 surface, intracellular protein, and mRNA expression in a time and concentration-dependent manner. The PPARδ induced ICAM-1 expression could be paralleled with a significantly increased T-cell adherence to the endothelial cells whereas PPARα failed to do so. Transcriptional activity studies using anICAM-1 reporter gene constructs revealed that PPARδ, but not PPARα agonists induced gene expression by stimulatingICAM-1 promoter activity via an Sp1 transcription factor binding site and inhibit the binding of the transcription factors Sp1 and Sp3. Furthermore, we performed mRNA stability assays and found that PPARα and PPARδ agonists increasedICAM-1 mRNA stability. Conclusion Therefore, our data provide the first evidence that PPARα and PPARδ agonists induce ICAM-1 expression in non-stimulated endothelial cells via transcriptional and posttranscriptional mechanisms.